Segmentation of Breast Tumor from Mammographic Images Using Histogram Peak Slicing Threshold - Dutta, Probal; Sarkar, Kanishka; Mandal, Ardhendu (International Journal of Computer Sciences and Engineering, 2025)
Medical image processing is a huge and challenging research field. Cancer of the breast is the most common among women in world wide. Mammography is a effectivediagnostic and screening tool to detect breast cancer at early stage. Mammograms use doses of ionizing radiation to create images like all X-rays. These images are then analyzed for any abnormal findings. Multiple research studies have been developed to improve cancer detection,diagnosis and evaluation.Over the last decade there has been a marked increased in the use of mammography to detect breast cancer. Various segmentation techniques have been used for detection of breast tumor from mammographic image in last decade. In this paper a method has been proposed based on histogram segmentation to detect the breast cancer from Mammographic images. The whole procedure has been done in MATLAB.